Can't block, must run: Small firms and appropriability - Justin Byma; Aija Leiponen (The Research Institute of the Finnish Economy (ETLA), 2006)
This empirical study examines small firms' strategies towards appropriating the returns to their investments in innovation and finds that they are qualitatively different from those found in earlier studies of more generally representative samples of firms. First, few of the smallest firms appear to benefit from patenting. Even within this sample of small firms, only the largest firms were likely to identify patents as the most important method of appropriating innovation returns. Thus, the strategic choice for most small firms is between secrecy and speed to market. The smallest firms and those in low technology or complex product industries tend to prefer speed, while small investments in R&D, discrete product technologies, and affiliation with higher technology industries explain preference for trade secrets. These results raise policy questions regarding the functioning of the existing systems of intellectual property rights when key policy goals include innovation by and growth of small firms. Furthermore, innovation policies that mandate collaboration are likely to significantly influence firms' appropriability strategies.
Keywords: O31; O34; L24; 330; SMEs; intellectual property rights; innovation; collaboration; Klein- und Mittelunternehmen; Immaterialgüterrechte; Innovation; Wettbewerbsstrategie; Finnland